Pelatihan pembuatan media pembelajaran berbasis Canva bagi guru-guru d SD Inpres Katara Kabupaten Malaka-NTT - Treesly Y.N Adoe; Jimylton Dethan; Gaudensius Jati Lamauran Koten; Habibi Musa (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
The quality of learning is greatly influenced by teachers' creativity in presenting teaching materials, especially in engaging and visual learning contexts. In the digital era, utilizing technologies like Canva is a solution to increase the effectiveness of material delivery. However, many teachers in 3T (frontier, outermost, and disadvantaged) areas, including Katara Elementary School in Malaka Regency, East Nusa Tenggara, have not yet optimally utilized this application due to limited knowledge and training. This community service program aims to provide training in creating Canva-based learning media to teachers at Katara Elementary School. The method used was participatory training through face-to-face workshops, live demonstrations, independent practice, and mentoring. The results of the activity showed a significant increase in teachers' understanding and skills in creating engaging visual learning media, such as infographics, educational posters, and interactive presentations. Most participants stated that this training was very helpful in supporting the learning process in the classroom. Thus, this training has had a positive impact on improving the quality of education in elementary schools, especially in remote areas. This activity also opens up opportunities for further collaboration and digital literacy development for teachers.